PENGARUH KOMPENSASI, DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. POLIPLAS INDAH SEJAHTERA, UNGARAN (Students' Journal of Economic and Management, 2014)
This study aims to examine and analyze the effect of compensation, work discipline and physical work environment on the performance of employees of PT. Poliplas Indah Sejahtera, Ungaran, Semarang regency. In this study, researchers used simple random sampling and sample rate and gain 94 employees. The test data used in this study include the product moment test validity, reliability testing with Alpha Cronbrach, multiple linear regression analysis, hypothesis testing to test and prove the research hypothesis. Data collected was tested for validity with product moment analysis method and tested reliability with coefficient alpha (Alpha Cronbrach), where the results of all data is valid and reliable. Results of analysis and discussion demonstrate that: 1 Compensation positive and significant effect on the performance of employees, the higher the compensation, the higher the performance of the employee; 2 Discipline of work positive and significant effect on the performance of the employee, the higher the labor discipline, the higher the performance of the employee; 3 physical work environment positive and significant effect onthe performance of the employee, the higher the motivation, the higher the employee's performance.Keywords: Compensation, Discipline of Work, Physical Work Environment, Employee Performance.